From Awareness to Behavior: The Empirical Effects of Real Problem-Oriented Learning in Civic and Moral Education - Xianghui Tian; Yanlin Tang (SAGE Open)
In this study, empirical research was conducted in the field of civic and moral education using a real problem-oriented learning methodology. The effectiveness of the methodology in enhancing students’ civic awareness and moral behavior was assessed through a randomized controlled trial (RCT). The study combined quantitative and qualitative methods to explore the impact of the instruction on students’ moral cognition and behavior. The results showed that the real problem-oriented model significantly enhanced students’ moral awareness and behavior, especially their moral judgment and problem-solving abilities, by engaging them in discussions and activities on real social issues, which provides a new practical idea for moral education. It should be noted that moral behavior is assessed mainly by observing students’ performance in social activities, while problem-solving ability is evaluated by analyzing their strategies for coping with moral dilemmas.